The impact of pre-hospital thrombolytic treatment on re-infarction rates: analysis of the Myocardial Infarction National Audit Project (MINAP) - Clive Weston (Heart, 2009)
The objective was to report on rate and predictors of re-infarction following thrombolytic treatment of ST-elevation myocardial infarction (STEMI) in an observational study of 35 356 patients treated by ambulance services and admitting hospitals in England and Wales and entered in the Myocardial Infarction National Audit Project (MINAP) in 2005–6.For 22 391 patients (63.3%) the presence or absence of re-infarction was recorded, and 1460 (6.5%) had re-infarction. Re-infarction rates were 6.5% for reteplase 6.4% for tenecteplase (6.4%); When the pre-hospital treatment to hospital arrival delay was greater than 30 minutes, re-infarction rates were 12.5% for reteplase, and 11.4% for tenecteplase. Re-infarction was more frequent after pre-hospital treatment with tenecteplase than reteplase (9.6% vs 6.6%, p = 0.005). After multivariate analysis independent predictors of re-infarction for tenecteplase were pre-hospital treatment, OR 1.44 (95% CI 1.21 to 1.71, p<0.001) and weight in the highest quartile compared to the lowest, OR 1.66 (95% CI 1.19 to 2.31, p = 0.003). For reteplase neither factor predicted re-infarction. Bleeding was less common with pre-hospital treatment—overall 1.8% against 3.1%; intracerebral bleeding 0.4% against 0.7%.Pre-hospital treatment with tenecteplase was associated with higher re-infarction rates. Longer intervals from pre-hospital treatment to arrival in hospital were associated with high re-infarction rates for both tenecteplase and reteplase.